Beginning programming - Kingsley-Hughes, Adrian (Wrox beginning guides., 2005)
Programming allows developers to create a sequence of instructions that enable computers to perform certain functions and tasks Offering the basic best practices and skills for novice programmers, this book helps readers gain new skills for writing programs and developing applications Teaches programming using C++ and explores scripting with JavaScript and VBScript, which are all free and don't require the reader to purchase any software Includes programming projects and real-world code examples that can be modified and expanded upon.